Bibliometric Analysis of Journal of Indian Education (2014–2019) A Study - Jain, Pooja (JOURNAL OF INDIAN EDUCATION, 2021)
The Journal of Indian Education (JIE) is the premier journal in the field of School Education being published in India by National Council of Educational Research and Training (NCERT), Delhi. Journal of Indian Education (JIE) has completed 45 years of its publication during the year 2019-20. This research paper studied the bibliometric analysis of Journal of Indian Education (JIE) during the period of five years 2014-2019. The data was collected from the NCERT website only. This journal is full-text available at NCERT website in open access from the year 2010 (complete set) onwards. This bibliometric study has covered the different aspects such as year-wise publication of article, pattern of authorship, degree of collaboration, average length of pages per article, average no. of references per article. This study analysed the data of five years (2014-19). Total 218 articles were published in 20 issues during the period of study. The collected data revealed that 17.43% articles were contributed during 2015-16 which is the minimum in all years and single authored contribution is highest and preferred with nearly 70 %. The degree of collaboration is 0.30. The average no. of pages per article is 13.30 and average no. of references per article is 19.40.